Pathogenic autoantibodies in the lambert-eaton myasthenic syndrome. - Lang, B; Pinto, A; Giovannini, F; Newsom-Davis, J; Vincent, A (2003)
Lambert-Eaton myasthenic syndrome (LEMS) is an autoimmune disorder of neuromuscular transmission in which antibodies are directed against voltage-gated calcium channels (VGCCs). We studied the action of LEMS immunoglobulin G (IgG) on cloned human VGCCs stably transfected into human embryonic kidney cells (HEK293). All LEMS IgGs tested bound to the surface of the P/Q-type VGCC cell line and caused a significant reduction in whole-cell calcium currents in these cells. By contrast, only 2 out of 6 IgGs bound extracellularly to the N-type VGCC cell line, and none of the LEMS IgGs tested was able to reduce whole-cell calcium currents in these cells. We used this apparent specificity of LEMS IgG for the P/Q-type VGCC to investigate the action of these IgGs on model systems where a number of different VGCC populations exist in equilibrium. LEMS IgG caused a significant downregulation in the omega-agatoxin IVA-sensitive P/Q-type VGCCs of cultured rat cerebellar neurons, but this was accompanied by a concomitant rise in the "resistant" R-type VGCCs. By using the passive transfer model of LEMS, similar results were observed at the mouse neuromuscular junction, where a significant reduction in P/Q-type VGCCs was paralleled by an increase in L- and R-type VGCCs. These results demonstrate an unexpected plasticity in the expression of VGCCs in mammalian neurons and may represent a mechanism by which the pathogenic effects of LEMS IgG are reduced.